(untitled) (Research, Society and Development, 2021)
The scarcity of water resources is the most limiting factor of agricultural production in the municipality of Estreito, MA. The irregularity in the distribution of rainfall during the year, which is characteristic of tropical regions, means that agricultural activity in Estreito, as well as in other cities in the state of Maranhão, reduces during the dry season. In view of this scenario, the search for means that aim to improve the efficiency of irrigation for the sustainable management of water becomes indispensable. The present study aimed to carry out a comparative study of the reference evapotranspiration estimation methods based on air temperature and solar radiation, with the standard Penman-Monteith method, in the municipality of Estreito - MA. The meteorological data necessary for the execution of this work were acquired from the database of the National Institute of Meteorology, using an eleven-year continuous historical series of the climatic elements that were used in the equations that make up the different methods. The reference evapotranspiration estimates for Penman-Monteith-FAO and the other methods were calculated. For the evaluation of the statistical performance of the models, the indicators of the correlation coefficient (r), determination coefficient (R²), agreement index (d) and the performance index (c) were used. The FAO 24, Turc and Makkink Radiation models showed better performance when compared to the standard Penman - Monteith method, and can serve as alternative methods for estimating reference evapotranspiration in the municipality of Estreito - MA.